Association of dipeptidyl peptidase-4 inhibitor and recurrent pancreatitis risk among patients with type 2 diabetes: A retrospective cohort study - Yang, Yi-Sun; Kornelius, Edy; Wang, Yu-Hsun; Lo, Shih-Chan; Huang, Chien-Ning (Frontiers in Pharmacology, 2024)
Introduction: Following the introduction of incretin-based drugs to the market, instances of acute pancreatitis have been reported, leading the FDA to mandate a warning label. Incretin-based therapy has been linked to a rare yet significant adverse event known as acute pancreatitis. However, these concerns of use of incretin therapy remained an ongoing debate. Methods: This retrospective cohort study was extracted data from the National Health Insurance (NHI) program in Taiwan focused on those having prior hospitalization history of acute pancreatitis. We identified adult patients with type 2 diabetes, all patients who received new prescriptions one year after the diagnosis of hospitalization for acute pancreatitis for DPP-4 inhibitors (index date). Study participants were divided into two groups: those taking DPP-4 inhibitors (the DPP-4 inhibitors group, n = 331) and those not taking DPP-4 inhibitors (the non- DPP-4 inhibitors group, n = 918). The outcome of interest is the recurrence of hospitalization of acute pancreatitis. Results: The incidence density (per 1000 person-years) of acute pancreatitis was 23.16 for DPP-4 inhibitors group and 19.88 for non-DPP-4 inhibitor group. The relative risk is 0.86 (95% confidence interval (CI) 0.53–1.38). Results from the Cox proportional hazard model (HR) analysis, the DPP-4 inhibitor was associated with a neutral risk of acute pancreatitis HR 0.68; 95% CI: 0.42–1.09. Conclusions: In this extensive nationwide cohort study conducted in Taiwan, involving a substantial number of newly diagnosed cases, the utilization of DPP-4 inhibitors appears to show no significant correlation with an elevated risk of acute pancreatitis, even among diabetic patients deemed to be at a high risk. These results extend the safety reassurance of incretin-based therapy to individuals considered high-risk for such complications.